Hubungan Pembelajaran Daring terhadap Keluhan Musculoskeletal Disorders (MSDs) pada Mahasiswa Keperawatan - Nursiam, Putri Sallamah; Sumeru, Annas; Alvian, Galih Noor (Holistic Nursing and Health Science, 2022)
Introduction: The implementation of online learning cannot be separated from the use of electronic devices (mobile phones, tablets or laptops) and internet connections. The duration and position of the student body during online learning are often not ergonomic, so there is a risk of Musculoskeletal Disorders (MSDs) complaints.The study to measure the effect of online learning to MSDs’ complaints yet performed, specifically in nursing. This study aims to analyze the relationship between the duration and body position of using a laptop/smartphone during online learning at Nursing Department in Unsoed. Methods: This research is a quantitative research with a cross sectional design. Subject was selected by using probability sampling technique with stratified random sampling of 129 respondents. The instrument used was a questionnaire on body position using a laptop, body position using a smartphone, and perceived MSDs complaints which were modifications of a similar research. Data was analyzed by somers’d test.Results: The results found there are significant relation between the duration of using a laptop/smartphone during online learning to MSDs complaints (p=0,001), body position using laptop during online learning to MSDs complaints (p=0,000), and body position using smartphone when online learning to MSDs complaints. (p=0,005).Discussion: There are significant relation between duration, body position using laptops, body position using smartphones with MSDs complaints at Nursing Department in Unsoed.